“Why Are We Different?” Feelings of Not Belonging and Actual Experiences of the Female Muslim Refugees in Lithuania - Jakucevičienė, Raminta (Tautosakos darbai, 2024)
The author of the article introduces materials that she has collected by means of making semi-structured in-depth interviews with female Muslim refugees, related to their experiences including interactions with the Lithuanian society and feelings of being different and unable to fit in. The women feel excluded because of their physical appearance, religion, and language. Refugees experience discrimination at work, public spaces as well as public transport, meanwhile their children, at school. The article aims at revealing certain models of estrangement internalized by the female refugees as well as their identification with their differences, on top of experiencing them. Muslim refugees attempt to fit in the recipient society and try to blend into the environment; their binding practices are affected by intersectional categories of identity, including gender, religion, race, and the status of a refugee. The Muslim women construct their identity against categories of similarity and difference in relation to the local society, finding ways of mellowing the feeling of not fitting in that they experience. However, while interacting with the Lithuanian society the female refugees, especially those that cannot speak Lithuanian or any other widely known language, frequently feel stigmatized, while the negative things that they experience, including deprecatory looks, insults and hostile physical actions (pushing or spitting) cause them to isolate themselves even further.